The Urban Built Environment, Walking and Mental Health Outcomes Among Older Adults: A Pilot Study - Roe, Jenny; Mondschein, Andrew; Neale, Chris; Barnes, Laura; Boukhechba, Medhi; Lopez, Stephanie (Frontiers in Public Health, 2020)
The benefits of walking in older age include improved cognitive health (e.g. mental alertness, improved memory functioning) and a reduced risk of stress, depression and dementia. However, research capturing the benefits of walking among older people in real-time as they navigate their world is currently very limited. This study explores cognitive health and wellbeing outcomes in older people as they walk in their local neighborhood environment. Two dichotomous settings were selected on the basis of significantly different infrastructure, varying levels of noise, traffic and percentage of green space. Employing a repeated-measures, cross over design, participants were randomly allocated to one of two groups, and walked on different days in an urban busy ‘grey’ district (a busy, built up commercial street) versus an urban quiet ‘green’ district (a quiet residential area with urban greenery). Our study captured real-time air quality and noise data using hand-held Airbeam sensors and physiologic health data using a smart watch to capture heart rate variability (a biomarker of stress). Cognitive health outcome measures were a pre- and post-walk short cognitive reaction time (SRT) test and memory recall of the route walked (captured via a drawn mental map). Emotional wellbeing outcomes were a pre- and post-walk mood scale capturing perceived stress, happiness and arousal levels. Findings showed significant positive health benefits from walking in the urban green district on emotional wellbeing (happiness levels) and stress physiology (p<0.05), accompanied by faster cognitive reaction times post-walk, albeit not statistically significant in this small sample. Cognitive recall of the route varied between the urban conditions with participants more likely to rely on natural features to define their routes when present. The environmental and physiologic data sets were converged to show a significant effect of ambient noise/ air pollutants and urban conditions on stress activation. Findings are discussed in relation to the complexity of combining real-time environmental and physiologic data and the implications for follow-on studies. Our study demonstrates new relationships between urban conditions, levels of noise / air pollution and stress activation and establishes a new protocol for exploring built environment - mental health associations in older people.